Analysis of the Short and Long Term Asymmetric Effects of Global Uncertainty Factors on BIST Stock Prices via the NARDL Method - Camgöz, Mevlüt (Maliye ve Finans Yazıları Yayıncılık Ltd. Şti., 2022)
The aim of this study is to examine the short and long-term asymmetric effects of global uncertainty factors on BIST stock prices, employing the NARDL (Nonlinear Autoregressive Distributed Lag) method. Implied volatility indices, which measure economic, geopolitical, energy, and financial risks, are used to represent global uncertainty factors. Empirical findings show that there is a long-term asymmetric cointegration relationship between all stocks and global uncertainty factors under investigation. In both long-term and short-term analyzes, uncertainty factors affect stock prices in different directions and extents asymmetrically. The findings will figure an important role in making asset allocation, diversification, risk management, and trading decisions for investors and portfolio managers.

Bu çalışmanın amacı global belirsizlik faktörlerinin BIST hisse senedi fiyatlarına olan kısa ve uzun dönem asimetrik etkilerinin NARDL (Nonlineer Gecikmesi Dağıtılmış Otoregresif) yöntemi kullanılarak ortaya konulmasıdır. Global belirsizlik faktörlerini temsilen ekonomik, jeopolitik, enerji ve finansal risklerin ölçüldüğü zımni volatilite endeksleri kullanılmıştır. Ampirik bulgulara göre, incelenen tüm hisse senedi fiyatları ile global belirsizlik faktörleri arasında uzun dönem asimetrik eşbütünleşme ilişkisi saptanmıştır. Hem uzun dönem hem de kısa dönem analizlerde, belirsizlik faktörleri hisse senedi fiyatlarını farklı yön ve ölçüde, asimetrik olarak etkilemektedir. Elde edilen bulgular yatırımcılar açısından varlık dağılımı, çeşitlendirme, risk yönetimi ve alım-satım kararlarının verilmesinde önemli bir rol oynayacaktır.
Global Belirsizlik Faktörlerinin BIST Hisse Senedi Fiyatlarına Asimetrik Etkilerinin NARDL Modeliyle Analizi
Keywords: Finance; Finans